PSYCHOLINGUISTIC RESEARCH: THE COMPARISON OF APPROACHES IN EUROPEAN, RUSSIAN AND UZBEKISTAN SCHOOLS OF LINGUISTICS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article analyzes the formation of psycholinguistics within European, Russian, and Uzbek linguistic schools, focusing on its main developmental directions and research objects. Methodological approaches, theoretical foundations, and the scientific views of leading representatives are comparatively examined, highlighting both their commonalities and distinctive features.